Effects of the pandemic (COVID-19) on the commercial sector of Pamplona Norte de Santander, a strategic view - Jaimes - Camacho, Frank Sebastián; Tuta - Ramírez, Laura Teresa; García - Hurtado, Dayanis (Universidad Francisco de Paula Santander, 2022)
The COVID 19 pandemic is one of the most important challenges the world has ever faced. From this context, it is necessary to consider that the company is part of the endogenous development of society, corporate social responsibility exceeds its role in the supply and demand of products and services. On the other hand, in Colombia, MSMEs represent an important sector of the economy, but it is also one of the most difficult in terms of sustainability; to this is added the effects of the COVID 19 crisis. Translated with www.DeepL.com/Translator (free version). The research was supported by postulates of Huguet (2020), Martin (2017), among others. It sought to perform a strategic analysis of the MSMEs of the commercial sector of Pamplona in times of pandemic (Covid-19), reviewing internal and external factors; matrices and semi-structured interviews were applied, to four key informants and an expert, with intentional selection. Descriptive, exploratory research, under a post-positivist paradigm, qualitative approach, phenomenological method. As a result, the state of the sector and of each company was identified, proposing action strategies.